Plasma Risperidone-related Measures in Children and Adolescents with Oppositional Defiant/Conduct Disorders - Piacentino, Daria (Clin Psychopharmacol Neurosci, 2020)
OBJECTIVE: Therapeutic drug monitoring helps clinicians in choosing the right drug and adjust its dose in specific patients. To this end, we aimed to assess time patterns of risperidone and its metabolite, 9-hydroxyrisperidone, in children and adolescents with oppositional defiant and/or conduct disorder. METHODS: We measured plasma concentrations of risperidone and 9-hydroxyrisperidone, their sum (active moiety, AM) and ratio, as well as plasma concentrations corrected for daily dose (C/D), from 140 children/adolescents with the above-mentioned disorders. We used Student’s t test to compare females versus males, patients under versus over 16-year-old, patients with lower versus higher than the median body weight, and patients with lower versus higher than the median body mass index (BMI). Two mixed-effects logistic regression models were fitted for risperidone/9-hydroxyrisperidone ratio and AM, respectively, by considering risperidone daily dose and patients’ demographic characteristics. RESULTS: Females had higher 9-hydroxyrisperidone and AM plasma concentrations than males (p = 0.004 and p = 0.034). Younger patients had lower risperidone plasma concentration and risperidone/9-hydroxyrisperidone ratio (p = 0.02 and p = 0.021), but higher C/D 9-hydroxyrisperidone and AM than older patients (p = 0.013 and p = 0.043). Lower-weight patients had lower plasma risperidone and risperidone/9-hydroxyrisperidone ratio (p = 0.014 and p = 0.019), but higher C/D 9-hydroxyrisperidone concentration than heavier patients (p = 0.03). All these results could be accounted for by daily dose. Patients with lower and higher BMI did not differ significantly. Regression analyses showed that only risperidone daily dose predicted risperidone/9-hydroxyrisperidone ratio, whereas risperidone daily dose, sex, and age predicted AM. CONCLUSION: Clinicians prescribing risperidone need to consider sex, age, and weight, but not BMI when adjusting daily doses.